O ensino da oralidade a partir da argumentação no gênero debate - Soares, Juliana Gurgel (2018)
The present study focuses on orality as an object of teaching through the use of the genre regulated debate, taking into account aspects and perspectives of argumentation. Our objective is to analyze how the teaching of orality can be systematized through the use of the debate genre ruled from the work with more recurrent argumentative techniques on it, to then propose teaching activities that grant the student the conscious use of the argumentation and allow it greater dominance of oral genres, such as debate. In the search for the scope of these propositions, we seek an approximation of Text Linguistics and Argumentation Theory with Teaching, since there is not only one theoretical perspective that contemplates all of our questions and allows us to arrive at what we aim at. So we rely mainly on the CAPES area document (2016) regarding Teaching as an area of knowledge; in Marcuschi (2001a; 2008), Marcuschi and Dionísio (2007), Bueno (2009) to deal with the question of oral teaching; and The New Rhetoric theory (Perelman, Tyteca, 2014) as a basis for discussions about argumentation. We developed a research of qualitative and documentary nature (MINAYO, 2001; GIL, 2008; GODOY, 1995) and as a methodological path to reach our objectives, we analyzed a political debate available on YouTube.com as an eminently argumentative oral genre in which we applied the analytical procedures based on Content Analysis (BARDIN, 1977). The results of the analysis process presented the existence of mishaps at the time of the production of the genre debate and, like Forte-Ferreira (2014), we categorized the data at the end of the analysis: previous preparation; time management; use of argumentative resources; based on them, we elaborated a plan of activities that includes a proposal for the constitution of debate societies in school, motivated by the reference found in the work done by the Brazilian Institute of Debates, as a path that can be traversed for a systematization of orality teaching through oral debate genre